If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(n + 1) + -3y(n + 1) + -4y(n) = 0 Reorder the terms: y(1 + n) + -3y(n + 1) + -4y(n) = 0 (1 * y + n * y) + -3y(n + 1) + -4y(n) = 0 Reorder the terms: (ny + 1y) + -3y(n + 1) + -4y(n) = 0 (ny + 1y) + -3y(n + 1) + -4y(n) = 0 Reorder the terms: ny + 1y + -3y(1 + n) + -4y(n) = 0 ny + 1y + (1 * -3y + n * -3y) + -4y(n) = 0 Reorder the terms: ny + 1y + (-3ny + -3y) + -4y(n) = 0 ny + 1y + (-3ny + -3y) + -4y(n) = 0 Multiply y * n ny + 1y + -3ny + -3y + -4ny = 0 Reorder the terms: ny + -3ny + -4ny + 1y + -3y = 0 Combine like terms: ny + -3ny = -2ny -2ny + -4ny + 1y + -3y = 0 Combine like terms: -2ny + -4ny = -6ny -6ny + 1y + -3y = 0 Combine like terms: 1y + -3y = -2y -6ny + -2y = 0 Solving -6ny + -2y = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2y' to each side of the equation. -6ny + -2y + 2y = 0 + 2y Combine like terms: -2y + 2y = 0 -6ny + 0 = 0 + 2y -6ny = 0 + 2y Remove the zero: -6ny = 2y Divide each side by '-6y'. n = -0.3333333333 Simplifying n = -0.3333333333
| 7b+9=-313 | | 1a+2b+3c=10 | | 2p+6=86 | | 2r^2-3r-4=0 | | 5z=90-2z | | 76+x+x+x=180 | | 2(3x-6)=3(2x-5) | | 75+x+x+x=180 | | a+270=-5a-6 | | 100x^3=10000000000 | | 9x-y+4z=-12 | | -5a-3=a+285 | | 2y^2-11y^1+12y=0 | | p-108=-2p-9 | | p-108=-29-9 | | 3x^2*3=0 | | -3e+8=e+80 | | 2r^2-11r+12=0 | | h+128=-2h+5 | | 0.89(x)-8.75=21-0.86(x) | | 9(3y-2)y=2 | | 5(x-3)+8=14(x)+2 | | 0.5a=5(1.25)12.50 | | t-103=-t-7 | | 2y^2-3y^1-4y=0 | | 0.8z=0.3z | | x^2+16k+60=5 | | -c-5=c+93 | | 2.5a=5(1.25)12.50 | | n-65=-n-9 | | 1n+2n= | | x-59=-x-9 |